Pola Pengembangan Kompetensi Profesional Guru di Unit Pelaksana Teknis Daerah Sekolah Pendidikan Formal SMP Negeri 5 Gunung Meriah - Lizamuddin, Lizamuddin; Pratiwi, Sri Nurabdiah; Amini, Amini (UMSU, 2025)
This study aims to determine the pattern of competency development of teacher professionalism in the regional technical implementation unit of the formal education school SMP Negeri 5 Gunung Meriah. The research used descriptive qualitative methods. Data collection techniques using observation, interviews and documentation and data analysis using the stages of data presentation, reduction and and conclusions. The results showed that the pattern of developing teachers' professional competence through supervision. The implementation of developing the professional competence of UPTD SPF SMP Negeri 5 Gunung Meriah teachers includes implementation through scientific work training including the ability of teachers to develop ideas and creativity so that teachers have competency development in teaching. Evaluating developing professional competence through supervision as an assessment of teacherprofessional competence development activities on the ability to develop material, structure, concepts, and scientific mindsets that support the subjects taught.